CATCHES OF MECHANISED BOATS AT MADRAS IN 1971-72 - Jayabalan, N; Devadoss, P (Indian Journal of Fisheries, 2011)
Fish catches by the mechanised vessels operated at Madras were estimatedfor the years 1971-72. The fishery, species composition and seasonal fluctuationin these two